Choroidal Thickness in Patients with Systemic Lupus Erythematosus Analyzed by Spectral-domain Optical Coherence Tomography. (3rd May 2016) - Altinkaynak, Hasan; Duru, Necati; Uysal, Betül Seher; Erten, Şükran; Kürkcüoğlu, Piraye Zeynep; Yüksel, Nilay; Duru, Zeynep; Çağıl, Nurullah
Abstract: Purpose : The aim of this study is to investigate the effect of systemic lupus erythematosus (SLE) on choroidal thickness (CT) in the subfoveal and perifoveal area as measured by enhanced depth imaging optical coherence tomography (EDI-OCT) in patients with SLE. Materials and methods : Fifty-eight patients with SLE (study group) and 58 healthy individuals (control group) were enrolled in the study. The subfoveal and perifoveal CT were measured by EDI-OCT. Results : The mean CT (μm) subfoveal, nasal, and temporal was 231.2 ± 57.6, 190.56 ± 30.64, and 222.65 ± 37.45 in the study group and 297.5 ± 45.1, 248.34 ± 39.67, and 286.54 ± 49.65 in the control group, respectively ( p  < 0.001, for all). Conclusion : The mean subfoveal, nasal, and temporal CT values were statistically significantly lower in patients with SLE when compared with healthy controls.